KAJIAN PUSTAKA PEMANFAATAN TUMBUHAN DALAM PENANGANAN MIOPIA - Yohana Tamba, Tantri
Myopia or nearsightedness is a long-distance vision disorder and is one of the most prevalent eye disorders in the world, especially in East Asia and Southeast Asia. Myopia can lead to further eye disorders such as low vision and blindness if left untreated and costs a significant amount of money for its treatment each year. However, there are no FDA or BPOM registered drugs that can be used for the treatment of myopia to date. Therefore, there is a need to find pharmacological interventions obtained from plants whose sources are abundant in nature. This literature review will discuss the empirical use of plants for myopia and plant-derived pharmacological interventions for myopia at the clinical and preclinical stages over the past 2 decades. In addition, this review will also discuss possible empirical used plants that have pharmacological activity against myopia. Literature searches were conducted using the search engines Scopus, Pubmed NCBI, and Google Scholar with the period starting from 2001 to the present. Based on the search results, it was found that there were 11 single plants and 3 plant combination formulas used empirically. There are also 7 plant/extracts/secondary metabolites that have proven pharmacological activity against myopia, namely 1 plant combination formula, Bu Jing Yi Shi: in vivo tested, 2 plant extracts (difrarel: in vivo and clinical trial tested and black currant extract: in vivo tested), and 4 secondary metabolites (clinically tested atropine, crocetin: in vivo and clinical trial tested, 7-methylxanthine and genipin: in vivo tested) that work against myopia with various mechanisms of action. In addition, Solanum torvum Sw. and Triphala are plant and plant combination used traditionally for myopia that may have pharmacological activity against myopia.